Clinical and Epidemiological Aspects on Healthcare-Associated Infections with Acinetobacter spp. in a Neurosurgery Hospital in North-East Romania - Nicoleta Luchian; Iulia Olaru; Alina Pleșea-Condratovici; Mădălina Duceac (Covrig); Mirela Mătăsaru; Marius Gabriel Dabija; Eva Maria Elkan; Vlad Andrei Dabija; Lucian Eva; Letitia Doina Duceac (Medicina, 2025)
Background and Objectives: Healthcare-associated infections (HAIs) are on the rise worldwide because the range of etiologic agents involved is very diverse and their antimicrobial resistance poses a threat to population health in the third millennium. Materials and Methods: We conducted a retrospective, longitudinal, descriptive clinical–epidemiological study in a hospital with a neurosurgical profile in northeastern Romania (“Prof. Dr. N. Oblu” Clinical Emergency Hospital in Iasi), during 2020–2024. The study is centered on the involvement of Acinetobacter spp. in the occurrence and evolution of HAIs. Results: The highest incidence of Acinetobacter spp. HAIs was recorded in the intensive care unit (ICU)—82.78% compared to neurosurgical wards (15.38%), with predominance in males (69.23%) and rural residence patients (55.67%). Most HAIs were represented by ventilator-associated pneumonia (42.13%) and lower respiratory tract infections (23.08%). Strains with high virulence and pathogenicity (CR-MDR, ESBL-MDR) were found, with the highest proportion of CR-MDR strains (88.27%). Conclusions: Our study provides useful data for surveillance of the antimicrobial resistance of pathogens involved in HAIs at the hospital level and for guiding antibiotic therapy in hospital-acquired infections.